Students’ perceptions of mathematics collaborative problem-solving session (MCPSS) at the foundation level - George Tan Geok Shim; Abdul Halim Abdullah; Ahmad Alif Kamal (Institute of Advanced Engineering and Science, 2026)
Collaborative problem-solving (CPS) skills are a vital component for students, especially in preparing them for future endeavors. It combines elements of collaborative and problem-solving skills into a single skill, emphasizing students’ ability to work together efficiently to solve everyday problems. While many studies have emphasized the importance of CPS, there remains a lack of research on students’ perceptions of its implementation in teaching and learning. The objective of the study is to determine students’ perceptions towards the mathematics collaborative problem-solving session (MCPSS) at a foundation center in Malaysia. The study utilized the mixed-method approach, using both a questionnaire and an interview to collect the data. The study sample consisted of 140 students randomly selected for a foundation center. Data from the study were analyzed using descriptive and thematic analysis. The study’s findings showed that most students held positive perceptions of the implementation of MCPSS in the mathematics course, with the majority of responses being between agreeing and strongly agreeing with the items related to meaningful learning, reflective learning, teamwork, and communication skills in MCPSS (SD=0.74–1.20). The outcome of the survey highlighted the overall acceptance of the students in the implementation of MCPSS in the mathematics foundation course.